Efeitos da substituição do farelo de soja por ureia encapsulada para bovinos de corte em confinamento - Thiago Alves Prado (2012)
Among the nutrients, protein is distinguished by its low concentrations in forages offered to animals in the dry season. Growing interest in the use of non-protein nitrogen sources (NPN) in supplementary feeding of ruminants representing an alternative in fulfilling the requirements for protein, with the possibility of reducing the cost of this nutrient in animal nutrition. This work aims to study the real effects of replacing soybean meal by encapsulated urea on live weight gain, nutrient intake, feed conversion, carcass yield, microbial protein synthesis in the rumen and apparent digestibility of nutrients used in diets of feedlot cattle. The experiments were performed at Estancia ABCZ (Brazilian Association of Zebu Breeders) during the period from July to November 2011. The animals used were beef cattle Nellore housed in individual pens. Were evaluated three experimental diets containing encapsulated urea at different levels of substitution of soybean meal: CON (control) - Forage + concentrate without encapsulated urea; UEP1 (Encapsulated Urea 1) - Forage + concentrate with encapsulated urea to 22% crude protein replacement soybean meal; UEP2 (Encapsulated Urea 2) - Forage + concentrate with encapsulated urea to 61% substitution of crude protein soybean meal. The diets were isocaloric and isonitrogenous. The experimental design was a randomized block design for the experiment 1 and experiment 2, we used a completely randomized design. Statistical analyzes were performed using orthogonal contrasts to compare and SNK test. In the first period (ADG1 - average daily gain 1) assessment UEP1 (2.616 kg / day) showed greater weight gain compared to CON (2.190 kg / day) which in turn did not differ from UEP2 (2.471 kg / day). The treatment UEP1 did not differ from UEP2. Over the next two periods (ADG2 and ADG3 - average daily gain 2 and 3, respectively) treatments showed similar response in weight gain and the last period (ADG4 - average daily gain 4) treatment UEP1 (1.867 kg / day ) again showed more performance compared to CON (1.395 kg / day). Treatment UEP2 (1.548 kg / day) did not differ from either of the two other treatments (UEP1 and CON). When we assessed the average daily gains together (ADG), UEP1 differed from CON treatment, being higher than the same. UEP1 was also superior to other treatments in feed efficiency. Treatment UEP2 showed higher consumption of neutral detergent fiber corrected for ash and crude protein (NDF) and digestible NDF (NDFapD) compared to the other treatments. The treatments did not differ for purine derivatives and estimates of microbial protein production, dry matter intake, digestibility of dry matter and organic matter, and nitrogen retention. The use of encapsulated urea as a replacement for soybean meal in low levels (22% of soybean meal CP) causes weight gain better than their non-inclusion, improving animal feed efficiency. It wasn't interference in apparent digestibility of foods, nitrogen retention and microbial protein production.